High-modulus graphene material and preparation method thereof
By designing a layered array structure and a central symmetrical graphic framework, combined with microchannel design, the shortcomings in mechanical and elastic properties of graphene materials are solved, and high modulus and high stability are achieved, which significantly improves its stress retention and durability.
Patent Information
- Application Number
- CN202510031861.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
AI Technical Summary
It is difficult to effectively assemble a single-layer graphene sheet into a bulk material with a macroscopic size while maintaining its excellent mechanical properties and rebound properties.
By designing a unique layered array structure and a stable central symmetrical graphic framework, combined with a customized microchannel design, a high modulus graphene material is formed. The material is closely arranged by a plurality of graphene units with a centrally symmetrical cross-section, each unit having an arched structure formed by a stack of curved graphene sheets, and the interfaces between the structural units are fused to each other.
The high modulus and high stability of graphene materials are achieved, the compression strength can reach 135 KPa, the modulus is 200 KPa, the stress retention rate reaches 94%, and the stress is maintained at 94% after 5,000 cycles, which significantly improves the mechanical properties and durability of the material.
Smart Images

Figure CN119797346A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of graphene materials, and in particular to a high-modulus graphene material and a preparation method thereof. Background Art
[0002] Graphene is a two-dimensional material composed of a single layer of carbon atoms tightly arranged in a honeycomb lattice structure with sp² hybrid orbitals. Since its first successful isolation in 2004, it has attracted widespread attention in the scientific and industrial communities due to its outstanding physical and chemical properties. Its unique properties include extremely high mechanical strength (Young's modulus of about 1TPa), excellent electrical and thermal conductivity, as well as excellent light transmittance and flexibility, which make graphene show great application potential in many fields. However, it is a major challenge for current research to effectively assemble single-layer graphene sheets into bulk materials with macroscopic dimensions while maintaining their excellent mechanical properties and resilience. Summary of the invention
[0003] In view of the above problems, the present invention proposes a high modulus graphene material and a preparation method thereof, which overcomes the deficiencies of the prior art graphene materials in mechanical properties and elastic properties. The present invention successfully overcomes this problem by designing a unique layered array structure and a stable central symmetric graphic skeleton, providing high modulus and high stability. In addition, the customized microchannel design also provides additional mechanical optimization space, which further improves its modulus.
[0004] One of the technical solutions of the present invention is to provide a high modulus graphene material. The graphene material is composed of a plurality of graphene units with centrally symmetrical cross-sections, each of which has an arched structure formed by stacking curved graphene sheets in a transverse direction, and the interfaces between the structural units are fused with each other.
[0005] The pure graphene material designed based on the present invention has a compressive strength of 135 KPa and a modulus of 200 KPa. After 5000 cycles, the stress retention rate is 94%. When the structural unit is in a triangular structure, it shows the highest modulus, at about 10 mg / cm 3 The density of aerogel is 388 kPa, which is much higher than other existing carbonaceous porous materials. When external force acts on aerogel, the C-shaped layered structure of aerogel itself can effectively resist the external force and maintain the stability of the structure. In addition, the triangular structure can effectively disperse these stresses and prevent damage caused by local stress concentration. This ability to disperse stress allows aerogel to withstand greater external forces without deformation. And the triangular structure has a higher stiffness and can resist deformation. In aerogel, this stiffness is converted into the modulus of the entire material. Therefore, aerogels with triangular structures usually have a higher modulus.
[0006] At the same time, when subjected to external forces, the triangular-structured aerogel can optimize energy dissipation through its unique skeleton structure. This energy dissipation mechanism helps reduce damage to the material during the stress process, thereby improving its durability.
[0007] The second technical solution of the present invention is to provide a method for preparing the above-mentioned graphene material, which specifically comprises the following steps: (1) A grid is provided at a fluid outlet, and a graphene oxide solution is extruded through the grid and pushed into a coagulation bath to obtain a graphene oxide metamaterial; each grid of the grid is centrally symmetrical, such as a triangle, a rhombus, a hexagon, a square, etc., and the grids are arranged in a matrix.
[0008] The grid can adjust the direction, speed and pressure of the liquid flow to precisely control the arrangement of the graphene oxide sheets to form a C-shaped arrangement. In addition, by adjusting the height and arrangement of the microchannels, as well as customizing structures such as triangles, the deformation mode of the material can be optimized and its modulus can be further improved. Immediately after extrusion, the edges of the graphene oxide in adjacent grids merge with each other.
[0009] (2) Reducing graphene oxide metamaterials to graphene metamaterials; (3) drying the graphene metamaterial; (4) The dried graphene metamaterial is heat treated at 300-2800°C. High temperature treatment can effectively release the residual stress between graphene sheets and improve the crystallinity and structural stability of the material. Through high temperature treatment, the arrangement of graphene sheets is further optimized, and the strength, modulus and resilience of the material are significantly improved.
[0010] Furthermore, the graphene oxide solution in step (1) is a pure graphene oxide solution or a mixed solution of graphene oxide and a polymer; the polymer is one of PAN, PAA, PVA and PVP, and the mass of graphene oxide in the solute of the graphene oxide solution is not less than 30%; the concentration of graphene oxide is 5.0 to 80.0 mg / mL.
[0011] Furthermore, the coagulation bath in step (1) is a metal salt solution or a polyamine solution, including one of calcium chloride, aluminum chloride, diamine, and triamine; the metal salt or polyamine undergoes a cross-linking reaction with graphene oxide. These high-valent metal salt solutions or polyamine solutions undergo a cross-linking reaction with graphene oxide, thereby enhancing the bonding force between the sheets. This cross-linking reaction not only fixes the arrangement of the graphene oxide sheets, but also improves the structural stability of the material, laying the foundation for subsequent reduction treatment and heat treatment.
[0012] Furthermore, the reduction method in step (2) is to react in a reducing agent with a concentration of 5wt% for 5 hours; the reducing agent is one of sodium ascorbate, hydroiodic acid, hydrobromic acid, tin dichloride and hydrazine hydrate. These reducing agents can effectively reduce graphene oxide while maintaining the ordered structure of its sheets. The reduction process not only improves the conductivity of the material, but also further enhances its mechanical properties.
[0013] Furthermore, the drying method in step (3) is freeze drying or drying at room temperature and normal pressure. The reduced graphene is placed in a freeze dryer for freeze drying. Freeze drying removes moisture by first freezing the water in the material into ice and then directly sublimating it into water vapor under a low pressure environment. Since the entire process is completed under low temperature conditions, it can effectively prevent volume shrinkage or structural collapse caused by water evaporation, ensuring that the three-dimensional network structure of graphene is completely preserved. Maintaining an intact microstructure helps to maximize the physical and chemical properties of graphene and thus enhance the overall performance of the material.
[0014] Beneficial effects of the present invention: The present invention arranges a plurality of graphene units with centrally symmetrical cross sections in an orderly manner to form a mutually supporting network structure, thereby greatly improving the modulus. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is the grid diagram of Example 3; Figure 2 is a cross-sectional view of Example 3; Figure 3 The plane perpendicular to the flow direction (x direction) and the plane in the flow direction (xz plane) of Examples 1-4; Figure 4 Mechanical performance diagram of Examples 1-4. DETAILED DESCRIPTION
[0016] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.
[0017] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.
[0018] The width of the grid in the present invention refers to the width of the grid itself in the extrusion direction of the graphene oxide solution ( Figure 1 ).
[0019] The coagulation bath used in the present invention is a commonly used coagulation bath in the art, including but not limited to calcium chloride, aluminum chloride, diamine, and triamine. As is common knowledge in the art, the concentration of the coagulation bath is generally 1 wt % to 10 wt %.
[0020] The embodiments of the present invention are further described below with reference to a plurality of embodiments.
[0021] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0022] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0023] Example 1 (1) A grid with hexagonal grids was placed at the extrusion outlet, and a 10 mg / mL aqueous graphene oxide solution was extruded through the grid into a calcium chloride coagulation bath. The free calcium on the graphene surface was then washed away with water multiple times to obtain a graphene oxide superstructure hydrogel; the spacing between the two sides of the hexagonal grid was 100 μm.
[0024] (2) immersing the graphene oxide superstructure hydrogel in step 1 in a 5 wt% sodium ascorbate solution, controlling the temperature at 80 °C, reacting for 5 hours to reduce the graphene oxide, and then washing the free ions on its surface with water for multiple times to obtain a gel-like graphene material; (3) freeze-drying the gel-like graphene material in step 2 to remove internal moisture and ensure the integrity of the structure, thereby obtaining a freeze-dried sample; (4) subjecting the freeze-dried sample in step 3 to a high temperature annealing treatment at 1000°C to obtain a hexagonal graphene material; After mechanical testing, the graphene material has a compressive strength of 135 KPa and a modulus of 200 KPa. After 5,000 cycles, the stress retention rate is 94%.
[0025] Example 2 (1) A grid with diamond grids was placed at the extrusion outlet, and a mixed aqueous solution of graphene oxide and PVA in a mass ratio of 5:5 was extruded through the grid into a calcium chloride coagulation bath. The graphene oxide concentration was 5 mg / mL. Subsequently, the free calcium on the graphene surface was washed away with water several times to obtain a graphene oxide superstructure hydrogel. The spacing between the two opposite sides of the diamond grid was 100 μm.
[0026] (2) immersing the gel-like graphene oxide material in step 1 in a 5 wt% tin dichloride solution, controlling the temperature at 80 °C, reacting for 5 hours to reduce the graphene oxide, and then washing the tin dichloride on its surface with water for multiple times to obtain a gel-like graphene material; (3) freeze-drying the gel-like graphene material in step 2 to remove internal moisture and ensure the integrity of the structure, thereby obtaining a freeze-dried sample; (4) The freeze-dried sample in step 3 is subjected to a high temperature annealing treatment at 2800° C. to obtain a diamond-shaped graphene material.
[0027] After mechanical testing, the graphene material's compressive strength reached 90 KPa and its modulus was 180 KPa. After 5,000 cycles, the stress retention rate was 93%.
[0028] Example 3 (1) A grid with a triangular grid is placed at the extrusion outlet, and a 10 mg / mL aqueous graphene oxide spinning solution is extruded through the grid into an aluminum chloride coagulation bath. The free aluminum on the graphene surface is then washed away with water multiple times to obtain a gel-like graphene oxide material; the side length of the triangular grid is 400 μm.
[0029] (2) immersing the gel-like graphene oxide material in step 1 in a 5 wt% hydroiodic acid / ethanol solution, controlling the temperature at 80 °C, reacting for 5 hours to reduce the graphene oxide, and then washing the hydroiodic acid on its surface with ethanol several times to obtain a gel-like graphene material; (3) freeze-drying the gel-like graphene material in step 2 to remove the internal moisture and ensure the integrity of the structure to obtain a freeze-dried sample; (4) The freeze-dried sample in step 3 is subjected to high temperature annealing at 1300°C to obtain a graphene material with a triangular cross section. Figure 2 and Figure 3 As shown, the graphene oxide is formed into a structural unit with a triangular cross section through a triangular grid, and then in the coagulation bath, each structural unit overlaps and bonds with each other to form a material composed of multiple triangular units. Each triangular unit is formed by stacking curved graphene sheets, and each graphene sheet is a triangle. The curved graphene sheet has good compressive resistance. After mechanical testing, the compressive strength of the graphene material reaches 85 KPa and the modulus is 523 KPa.
[0030] Example 4 (1) A grid with square grids was placed at the extrusion outlet, and a mixed aqueous solution of graphene oxide and PAA in a mass ratio of 3:7 was extruded through the grid into a diamine coagulation bath, with a graphene oxide concentration of 15 mg / mL. The diamine on the graphene surface was then washed off with water several times to obtain a gel-like graphene oxide material; the square grid became 400 μm.
[0031] (2) immersing the gel-like graphene oxide material in step 1 in a 5 wt% hydrazine hydrate solution, controlling the temperature at 80 °C, reacting for 5 hours to reduce the graphene oxide, and then washing the hydrazine hydrate on its surface with ethanol several times to obtain a gel-like graphene material; (3) freeze-drying the gel-like graphene material in step 2 to remove the internal moisture and ensure the integrity of the structure to obtain a freeze-dried sample; (4) The freeze-dried sample in step 3 is subjected to a high-temperature annealing treatment at 300° C. to obtain a graphene material with a square cross-section.
[0032] Example 5 (1) A grid with triangular grids was placed at the extrusion outlet, and a mixed aqueous solution of graphene oxide and PAN in a mass ratio of 5:5 was extruded through the grid into a triamine coagulation bath, with a graphene oxide concentration of 80 mg / mL. The triamine on the graphene surface was then washed off with water several times to obtain a gel-like graphene oxide material; the triangular grid became 400 μm.
[0033] (2) immersing the gel-like graphene oxide material in step 1 in a 5 wt % hydrobromic acid solution, controlling the temperature at 80 ° C, reacting for 5 hours to reduce the graphene oxide, and then washing the hydrobromic acid on its surface with ethanol several times to obtain a gel-like graphene material; (3) freeze-drying the gel-like graphene material in step 2 to remove the internal moisture and ensure the integrity of the structure to obtain a freeze-dried sample; (4) The freeze-dried sample in step 3 is subjected to a high-temperature annealing treatment at 1400° C. to obtain a graphene material with a triangular cross-section.
[0034] Example 6 (1) A grid with triangular grids was placed at the extrusion outlet, and a mixed aqueous solution of graphene oxide and PVP with a mass ratio of 6:4 was extruded through the grid into a triamine coagulation bath. The concentration of graphene oxide was 60 mg / mL. The triamine on the surface of graphene was then washed off with water several times to obtain a gel-like graphene oxide material. The side length of the triangular grid was 400 μm.
[0035] (2) immersing the gel-like graphene oxide material in step 1 in a 5 wt% hydrazine hydrate solution, controlling the temperature at 80 °C, reacting for 5 hours to reduce the graphene oxide, and then washing the hydrazine hydrate on its surface with ethanol several times to obtain a gel-like graphene material; (3) freeze-drying the gel-like graphene material in step 2 to remove the internal moisture and ensure the integrity of the structure to obtain a freeze-dried sample; (4) The freeze-dried sample in step 3 is subjected to a high-temperature annealing treatment at 1200° C. to obtain a graphene material with a triangular cross-section.
[0036] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.
Claims
1. A high modulus graphene material, characterized in that: It is composed of a plurality of graphene units with centrally symmetrical cross sections, each of which has an arched structure formed by stacking curved graphene sheets in a lateral direction, and the interfaces between the structural units are fused with each other.
2. The graphene material according to claim 1, characterized in that: The centrally symmetrical figures are triangles, squares, rhombuses, hexagons or octagons.
3. A method for preparing a graphene material according to claim 1, characterized in that: The following steps are involved: (1) a grid is provided at the fluid outlet, a graphene oxide solution is extruded through the grid, and pushed into a coagulation bath to obtain a graphene oxide metamaterial; each grid of the grid is centrally symmetrical, and the grids are arranged in a matrix; (2) Reducing graphene oxide metamaterials to graphene metamaterials; (3) drying the graphene metamaterial; (4) Heat treating the dried graphene metamaterial at 300-2800°C.
4. The preparation method according to claim 3, characterized in that: The graphene oxide solution in step (1) also includes a polymer; the polymer is one of PAN, PAA, PVA and PVP, and the mass of graphene oxide in the solute of the graphene oxide solution is not less than 30%; the concentration of graphene oxide is 5.0 to 80.0 mg / mL.
5. The preparation method according to claim 3, characterized in that: The coagulation bath in step (1) is a metal salt solution or a polyamine solution, including one of calcium chloride, aluminum chloride, diamine, and triamine; the metal salt or polyamine undergoes a cross-linking reaction with graphene oxide.
6. The preparation method according to claim 3, characterized in that: The reduction method in step (2) is to react in a reducing agent with a concentration of 5 wt % for 5 hours; the reducing agent is one of sodium ascorbate, hydroiodic acid, hydrobromic acid, tin dichloride and hydrazine hydrate.
7. The preparation method according to claim 3, characterized in that: The drying method in step (3) is freeze drying or drying at room temperature and normal pressure.
Citation Information
Patent Citations
Graphene oxide solution for wet spinning and preparation method thereof, graphene fiber and preparation method of graphene fiber
CN105088415A
Method for preparing graphene-based carbon fibers at room temperature
CN113136640A
Graphene material with both high strength and high toughness and preparation method thereof
CN113151935A
Aerogel fiber with specific section morphological characteristics and preparation method and device thereof
CN114250529A
Graphene assembly fiber as well as preparation method and application thereof
CN114990734A
Cited By
Sealing ring and preparation method thereof
CN120027207A
A sealing ring and a method for manufacturing the same
CN120027207B